Oral History Interview: Joe Zaragoza - Zaragoza, Joe; Jagels, Stacey
Interviewee: Joe Zaragoza; Place of Birth: Kern County; Interviewer: Stacey Jagels; Date of Interview: February 5, 1981; Place of Interview: Bakersfield, California; Number of Tapes: 1; Transcriber: Barbara Mitchell